Unraveling Universalist Perspectives on Teaching and Caring for Infants and Toddlers: Finding Authenticity in Diverse Funds of Knowledge. Issue 1 (2nd January 2018) - Recchia, Susan L.; McDevitt, Seung Eun
ABSTRACT: Although child-rearing beliefs and practices vary widely across cultures, a dominant discourse on how to teach and care for young children undergirds most early childhood teacher education programs. In this qualitative multicase study, the authors explored the ways that immigrant preservice teachers negotiated their emerging teacher identities across discontinuities between their own funds of knowledge and the theory and practice presented in their infant and toddler practicum course. Using a funds of identity framework, the authors drew on multiple data sources to examine how three immigrant students questioned, complicated, expanded on, connected, and/or denied their funds of knowledge as they redefined their professional sense of themselves as teachers. Findings indicate that creating a hybrid space within a teacher education practicum course allowed immigrant preservice teachers to comfortably bring their funds of knowledge, critically reflect on their own practice, and authentically develop their emerging teacher identities. Implications are discussed, focusing on the importance of understanding the impact and contribution of teachers' personal knowledge, the fluidity of immigrant students' thinking within a hybrid learning space, and the need for teacher education programs that openly invite and honor immigrant preservice teachers' diverse funds of knowledge to help them find authenticity in teaching and learning.